Social Justice Education and U.S. Military Adult Learners - Royce Ann Collins; Susan Yelich Biniecki; Cheryl Polson (Adult Education Research Conference, 2016)
The purpose of this paper is to examine the Veteran or active duty military adult learner in higher education through the lens of social justice education, intersectionality, and microaggressions.
Keywords: veteran; active duty military; adult learner; intersectionality; microaggressions